2017
DOI: 10.1007/978-3-319-66179-7_73
|View full text |Cite
|
Sign up to set email alerts
|

CASED: Curriculum Adaptive Sampling for Extreme Data Imbalance

Abstract: We introduce CASED, a novel curriculum sampling algorithm that facilitates the optimization of deep learning segmentation or detection models on data sets with extreme class imbalance. We evaluate the CASED learning framework on the task of lung nodule detection in chest CT. In contrast to two-stage solutions, wherein nodule candidates are first proposed by a segmentation model and refined by a second detection stage, CASED improves the training of deep nodule segmentation models (e.g. UNet) to the point where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…It has been empirically demonstrated that this learning paradigm is useful in avoiding bad local minima and in achieving better generalization ability [134]. Data curriculum learning has recently been used in several medical applications, especially location and classification tasks [78], [135]- [137] but few in segmentation tasks [138], [139]. To train a deep network for the classification and location of thoracic diseases on chest radiographs, Tang et al [135] first ranked the training images according to the difficulty (indicated by the severity-levels of the disease) and then fed them to the deep network to boost the representation learning gradually.…”
Section: Curriculum Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been empirically demonstrated that this learning paradigm is useful in avoiding bad local minima and in achieving better generalization ability [134]. Data curriculum learning has recently been used in several medical applications, especially location and classification tasks [78], [135]- [137] but few in segmentation tasks [138], [139]. To train a deep network for the classification and location of thoracic diseases on chest radiographs, Tang et al [135] first ranked the training images according to the difficulty (indicated by the severity-levels of the disease) and then fed them to the deep network to boost the representation learning gradually.…”
Section: Curriculum Learningmentioning
confidence: 99%
“…In addition to the predefined curriculum by prior knowledge and keeping it fixed after that, the curriculum can also be dynamically determined to adapt to the feedback of the learner, also known as self-paced curriculum learning [141] or self-paced learning [142]. For lung nodule segmentation/detection with extreme class imbalance, Jesson et al [138] introduced an adaptive sampling strategy, which favors difficult-to-classify examples. For instance-level segmentation of pulmonary nodule, Wang et al [139] employed pseudo labels as the surrogate of ground truth labels on unlabeled data.…”
Section: Curriculum Learningmentioning
confidence: 99%
“…CASED performs adaptive curriculum sampling to solve the problem of highly data imbalance and makes it possible for the model to distinguish nodules from immediate proximity and subsequently enlarges the hard-declassified global context, up to uniform categories in the empirical data pool. In this way, CASED is the most performant and is used in the detection of pulmonary nodules in thoracic CT [165].…”
Section: Paternal Training Is the Resolution Of Tasks With Increasing Difficulties That Use Curricular Learning To Identify And Locate Lementioning
confidence: 99%
“…Recently, the idea of curriculum learning has been utilised for medical imaging challenges. Jesson et al (2017) proposed to use patches of different complexity to train a network for lung nodule detection. Their algorithm learnt how to distinguish nodules from the initial surroundings and added difficult patches gradually.…”
Section: Related Workmentioning
confidence: 99%